Electromyography - A Reliable Technique for Muscle Activity Assessment - Hussain, J.; Sundaraj, K.; Low, Y. F.; Lam, C. K.; Ali, Md. A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
In recent years, many questions have been raised on the credibility of Electromyography (EMG) as a technique to evaluate muscle activity, particularly by sports and fitness community. This questioning goes farther when it comes to surface electromyography (sEMG). This paper covers an overview of EMG, addresses some basic concepts and provide rudiment for research. Muscle activity assessment through EMG has been reviewed in terms of the type of movements. There are few limitations to EMG but these confines are addressable. The problem rather lies in the interpretation and generalization of that data. Limitations are there in every technology, precautionary measures must be taken to avoid those while using it. Reservations about EMG have been summarized along with their responses. A few techniques to analyze EMG data, and possibilities to extrapolate and interpret, are also provided. Current perspectives and practical applications of EMG and sEMG are also part of this article.